Development and Mixed-Methods Evaluation of a Pain Assessment Video Training Program for Long-Term Care Staff - Michelle M Gagnon; Thomas Hadjistavropoulos; Jaime Williams (Pain Research and Management)
INTRODUCTION: Inadequacies in pain assessment and management in long-term care have been well documented. Insufficient pain education and inaccurate beliefs about the nature of pain and aging have been identified as possible contributors. The present study addresses the need for improved, efficient and feasible continuing pain education through the use of an assessment training video.